2023
DOI: 10.1038/s41415-023-6232-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of dentists' psychological wellbeing during the COVID-19 pandemic

Brett Lefkowitz,
Jonathan Houdmont,
Alec Knight

Abstract: Background The COVID-19 pandemic presented significant challenges to healthcare workers worldwide, including the effect on the psychological wellbeing of dentists.Aims To evaluate the impact of the early phases of the pandemic on the psychological health, long-term wellbeing and clinical service provision of dentists, as well as the identification of the key risk and protective factors for adverse mental health outcomes (MHOs) in this group.Methods A systematic review of cross-sectional studies (n = 53) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…41 A recent systematic review of dentists' psychological well-being during the COVID-19 pandemic identi ed age as a risk factor for adverse mental health outcomes in this group. 7 Gasparro et al postulated that younger, less experienced dentists were more likely to develop psychological symptoms of anxiety and depression. 42 Zhao et al concluded that with increase in age, the frontline dental staff were less likely to suffer from anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 A recent systematic review of dentists' psychological well-being during the COVID-19 pandemic identi ed age as a risk factor for adverse mental health outcomes in this group. 7 Gasparro et al postulated that younger, less experienced dentists were more likely to develop psychological symptoms of anxiety and depression. 42 Zhao et al concluded that with increase in age, the frontline dental staff were less likely to suffer from anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…6 There was considerable psychological impact of the pandemic on the mental health outcomes of dentists worldwide as well. 7 Prior to the COVID-19 pandemic, literature has reported high rates of suicidality, burnout, stress, anxiety and depression among dentists. 8,9 Dental settings present a potentially high risk of COVID-19 cross-infection as dental care workers work in closed environments and conduct aerosol-generating procedures.…”
Section: Introductionmentioning
confidence: 99%